Successful treatment of a pure red-cell aplasia patient with γδT cells and clonal TCR gene rearrangement: A case report - Li, Xian; Zhu, Xinyi; Zhang, Xiaohong; Wang, Weiqin (Frontiers in Immunology, 2023)
Pure red-cell aplasia (PRCA) is a syndrome associated with reduced erythroid precursors. This report presents the case of an elderly PRCA patient with significantly proliferated γδΤ cells and clonal T-cell receptor (TCR) gene rearrangement. The cause of this patient’s PRCA was confirmed to be an autoimmune disorder rather than malignancy on the basis of flow cytometry, TCR gene rearrangement, and positron emission tomography/computed tomography (PET/CT) findings. Moreover, the γδΤ cell group identified in this case was captured for the first time under the microscope; this CD4+/CD8- (extremely high CD4/CD8 ratio) population is rare in PRCA patients. Our patient with a monoclonal and polyclonal hybrid of TCR gene rearrangement was sensitive to Cyclosporin A (CsA), despite previous reports suggesting that patients with TCR clonal rearrangement may respond poorly to this drug. Overall, this case presents valuable clinical findings for the future diagnosis and management of PRCA caused by autoimmune conditions and further research on γδΤ cells’ autoimmune pathophysiology and gene rearrangement.